Cardiovascular predictors associated with poor short-term prognosis in patients diagnosed with SARS-CoV-2 in Spain. (14th October 2021) - Esteban-Lucia, L; Devesa-Arbiol, A; Zambrano Chacon, M A; Venegas Rodriguez, A M; Gonzalez-Rodriguez, M; Maure-Blesa, L; Avila-Barahona, P; Pello-Lazaro, A M; Gonzalez-Lorenzo, O; Fernandez-Roblas, R; Villar-Alvarez, F; Ibanez, B; et al.
Abstract: Background: On January 2020, the first patient with coronavirus 2 (SARS-CoV-2) was detected in Spain. Since then, 3 280 000 cases have been confirmed and 75.305 people have died. We aimed to clarify the epidemiological and clinical characteristics related with poor short-term prognosis in patients diagnosed with SARS-CoV-2. Methods: Observational, retrospective single-center study including consecutive patients (≥40yo) diagnosed with SARS-CoV-2 through PCR, since March 2nd to 20th 2020 in our center in Spain. The primary endpoint (PE) was the combined of all-cause death or need for orotracheal intubation within the first 30 days of infection symptoms. Results: 704 patients were included (table). A follow-up period of thirty-days was fully completed in 692 of 704 patients (98.3%). At the end of this period, 148 patients (21.4%) met the PE; they were older, more frequently male, obese and smokers. Patients who met the PE had a higher prevalence of hypertension, diabetes, dyslipidemia, ischemic heart disease, heart failure, peripheral and cerebrovascular disease, cancer and lung pathologies. They received more frequently therapies with renin-angiotensin system inhibitors, betablockers, calcium channel blockers and statins, as well as antiplatelet and anticoagulant therapies Multivariate analysis showed that age (OR 1.99 for every 10 years, 95% CI [1.637–2.4], p<0.001), female sex (OR 0.49, [0.30–0.80], p=0.004), diabetes (OR 2.09, [1.17–3.71], p=0.012), lung disease (OR 1.99, [1.14–3.44], p=0.014) and body mass index (OR 1.33 for each 5 kg/m 2 increased, [1.05–1.68], p=0.017) were predictors of the PE. Hypertension was not significantly related to the PE (OR 1.55, [0.93–2.60], p=0.09) Conclusion: In our group of patients with SARS-CoV-2, age, male sex, diabetes, lung disease and obesity were found to be independent predictors of the combined of all case death or need for orotracheal intubation within the first 30 days of infection symptoms. Larger studies are needed to confirm these results. FUNDunding Acknowledgement: Type of funding sources: None.